A method to discriminate between closely related bovine major histocompatibility complex class I alleles by combining established PCR‐SSP assays with RFLPs. Issue 4 (23rd February 2015) - Svitek, N.; Nzau, B.; Steinaa, L.; Nene, V.
Abstract: We have developed a polymerase chain reaction‐sequence‐specific primers‐restriction fragment length polymorphism (PCR‐SSP‐RFLP) method to rapidly differentiate between the A18 and A18 variant (v) BoLA haplotypes and between A14 and A15/A15v BoLA haplotypes in Holstein/Friesian cattle. We used published SSP to PCR amplify BoLA alleles expressed in animals of known haplotype and exposed the amplicons to the restriction enzyme Pvu II that was predicted to cut at a unique site in the middle of BoLA‐6*01302 (A18v) and BoLA‐1*00901 (A15) but not in BoLA‐6*01301 (A18) or BoLA‐1*02301 (A14) alleles. Whereas the method does not discriminate between the A15 and A15v haplotypes, as the BoLA‐1*00902 allele associated with A15v also contains a Pvu II site, we are interested in cattle of A18 and A14 haplotype for vaccine related studies. Our results also indicated that the BoLA‐6*01302 (A18v) allele is much more abundant than BoLA‐6*01301 (A18) in the cattle that we sampled.